Metaphor, Meaning and Translation - Cristofoli, Mirella; Dyrberg, Gunhild; Stage, Lilian (HERMES - Journal of Language and Communication in Business, 1998)
Over the last decades, metaphor has been subject to intensive research within philoso-phy, psychology, psychiatry, pedagogics, etc., whereas there has been less focus on the study of metaphor as a linguistic utterance. But to a translator metaphor is a very intriguing practical linguistic problem. How do we translate for instance the Danish metaphor blæksprutte? In this article, we will discuss to what extent ordinary dictionaries may be of use (can you look up the metaphor blæksprutte?) and will describe the data-base of metaphors that we are establishing with examples from economic and political texts in Danish, French and Italian. The database is organized as a thesaurus where metaphorical utterances are categorized under Meaning and Source domain and where translators may find inspiration when having to render metaphors in the three lan-guages.